Advancing sustainable wheat production in the Andes through biofertilization with Azospirillum, Trichoderma, and fermented anchovy-based inputs under rainfed conditions - Villegas Carrasco, Edwin Raúl (2026)
Wheat (Triticum aestivum L.) sustains global caloric intake, but its productivity in Andean highlands is constrained by soil fertility and input reliance. This study represents one of the first field-based evaluations of biofertilizers under high-altitude, rainfed Andean conditions, addressing a major knowledge gap in low-input mountain agroecosystems. This study evaluated three seed-applied biofertilizers—Azospirillum brasilense, Trichoderma viride (Trichomax), and an anchovy (Engraulis ringens) based liquid biofertilizer, compared with an untreated control and a soil-test mineral fertilization benchmark in rainfed wheat (Triticum aestivum L.) cv. INIA 405 in the central Andes of Peru. A 5 × 5 Latin square design (25 plots) was established under farmer-realistic conditions. At physiological maturity (Zadoks 9.5), plant height, spike length, grains per spike, thousand-grain weight, test weight, root dry mass, and grain yield were recorded. Mineral fertilization achieved the highest yield (1.20 ± 0.79 t ha⁻¹), nearly doubling the control (0.60 ± 0.47 t ha⁻¹). Notably, A. brasilense delivered an intermediate yield of 0.90 ± 0.64 t ha⁻¹, representing a 50% increase over the control—accompanied by a marked rise in root dry mass. T. viride and the anchovy-based input yielded 0.85 ± 0.59 and 0.81 ± 0.59 t ha⁻¹, respectively. Grain physical quality remained stable across treatments (thousand-grain weight ≈ 42 g; test weight 68–75 kg hL⁻¹). Trait responses were complementary: root dry mass increased with mineral fertilization and A. brasilense, whereas spike length increased with mineral fertilization and the anchovy-based input. Overall, the evidence supports biofertilizers, particularly A. brasilense, as effective complements that enable partial fertilizer substitution within integrated nutrient-management strategies for sustainable wheat production in Andean rainfed systems.